Modeling Backscattering Behavior of Vulnerable Road Users Based on High-Resolution Radar Measurements - Abadpour, Sevda (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2023)
During the evolvement of autonomous driving technology, obtaining reliable 3-D environmental information is an indispensable task in approaching safe driving. The operational behavior of automotive radars can be precisely evaluated in a virtual test environment by modeling its surrounding, specifically vulnerable road users (VRUs). Such a realistic model can be generated based on the radar cross section (RCS) and Doppler signatures of a VRU. Therefore, this work proposes a high-resolution RCS measurement technique to determine the relevant scattering points of different VRUs.